2019
DOI: 10.13057/nusbiosci/n110109
|View full text |Cite
|
Sign up to set email alerts
|

Ethanolic extract of mangosteen (Garcinia mangostana) pericarp as sensitivity enhancer of doxorubicin on MCF-7 cells by inhibiting P-glycoprotein

Abstract: Abstract. Laksmiani NPL. 2019. Ethanolic extract of mangosteen (Garcinia mangostana) pericarp as sensitivity enhancer of doxorubicin on MCF-7 cells by inhibiting P-glycoprotein. Nusantara Bioscience 11: 49-55. Generally, doxorubicin is used in combination with other anticancer agents. Reduction side effects tend to be better in combination use than the use of single doxorubicin. Therefore the development of anticancer agents with low side effects and combination agents that decrease the side effects of doxorub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Similarly, other studies have shown an enhanced effect of chemotherapeutic agents when combined with AM in different tumors [31][32][33][34][35][36]. Particularly in breast cancer MCF-7 cells, the combination of doxorubicin with mangosteen derivatives has resulted in improved antineoplastic effects [38], including the reduction of stemness and the induction of cell death [37]. The above, together with our results, strongly support the concept that AM could act as an adjuvant of conventional chemotherapy.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similarly, other studies have shown an enhanced effect of chemotherapeutic agents when combined with AM in different tumors [31][32][33][34][35][36]. Particularly in breast cancer MCF-7 cells, the combination of doxorubicin with mangosteen derivatives has resulted in improved antineoplastic effects [38], including the reduction of stemness and the induction of cell death [37]. The above, together with our results, strongly support the concept that AM could act as an adjuvant of conventional chemotherapy.…”
Section: Discussionsupporting
confidence: 87%
“…The above suggests that the xanthone could act as an adjuvant agent of conventional chemotherapy. Regarding breast cancer, there are only two reports studying the effects of the ethanolic extract of mangosteen or AM combined with doxorubicin [37,38]. However, to our knowledge, there are no studies looking specifically at the combination of AM in combination with 5-FU in breast cancer cells with different phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…The pericarp of mangosteen has been used in Indonesia as a cholesterol-lowering agent, and we have observed that the active compound of mangosteen's pericarp (alpha-mangostin) has anticancer and antifibrosis activities. 13,14 Moreover, alpha-mangostin is also known to have anti-oxidant, anti-inflammatory, hypo-allergenic, and antifungal activities. 15,16 However, to the best of our knowledge, it is not yet known whether alpha-mangostin can prevent cardiac hypertrophy and fibrosis due to diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…The possible mechanism was via interaction with the Pgp transporter. This interaction was confirmed by Laksmiani [22], who demonstrated an affinity of α-MG to Pgp by molecular docking. After the interaction, the test compounds inhibited Pgp efflux transport, which appeared as a noncompetitive inhibitor of substrate transport.…”
Section: Discussionmentioning
confidence: 66%
“…Previous studies have indicated the capacity of some xanthone scaffolds to alter Pgp [ 19 , 20 , 21 ]. Recently, Laksmiani [ 22 ] found that ethanolic extract of mangosteen pericarp (EEMP) in combination with doxorubicin increased the cytotoxic activity of doxorubicin in MCF-7 cells. The in silico assay by molecular docking with the AutoDock 4.2 program revealed that α-mangostin (as the active compound of EEMP) had an affinity for Pgp with binding energy of −6.13 kcal/mol, and the researcher suggested that an in vitro assay of α-mangostin in inhibiting Pgp activity should be conducted.…”
Section: Introductionmentioning
confidence: 99%